An Analysis of Pedestrian Accidents in Sabarkantha District - Mitesh Patel; Kartha Girija; HK Mehta (Medsci Publications, 2010)
The study of the road traffic accidents on selected highways and town/village roads of Sabarkantha district, Gujarat was conducted for the period of one year (from January 2002 to December 2002), during this period, total 512 event of road traffic accidents were recorded in the district, It is observed that the Pedestrian accident (37.78%) dominates overall the other types of accidents. Among the 193 events of Pedestrian accident, 158(81.87%) were non-fatal and 35(18.13%) fatal. The maximum number of events (62.69%) took place during daytime and 37.31% of events took place during dark hours. Analysis also shows that highest number of events (35.23%) took place on town/village roads.